Reactivity to unpredictable threat as a treatment target for fear-based anxiety disorders. Issue 14 (24th April 2017) - Gorka, S. M.; Lieberman, L.; Klumpp, H.; Kinney, K. L.; Kennedy, A. E.; Ajilore, O.; Francis, J.; Duffecy, J.; Craske, M. G.; Nathan, J.; Langenecker, S.; Shankman, S. A.; et al.
Abstract : Background: Heightened reactivity to unpredictable threat (U-threat) is a core individual difference factor underlying fear-based psychopathology. Little is known, however, about whether reactivity to U-threat is a stable marker of fear-based psychopathology or if it is malleable to treatment. The aim of the current study was to address this question by examining differences in reactivity to U-threat within patients before and after 12-weeks of selective serotonin reuptake inhibitors (SSRIs) or cognitive-behavioral therapy (CBT). Methods: Participants included patients with principal fear ( n = 22) and distress/misery disorders ( n = 29), and a group of healthy controls ( n = 21) assessed 12-weeks apart. A well-validated threat-of-shock task was used to probe reactivity to predictable (P-) and U-threat and startle eyeblink magnitude was recorded as an index of defensive responding. Results: Across both assessments, individuals with fear-based disorders displayed greater startle magnitude to U-threat relative to healthy controls and distress/misery patients (who did not differ). From pre- to post-treatment, startle magnitude during U-threat decreased only within the fear patients who received CBT. Moreover, within fear patients, the magnitude of decline in startle to U-threat correlated with the magnitude of decline in fear symptoms. For the healthy controls, startle to U-threat across the two time points was highly reliable and stable. Conclusions: Together, these results indicate that startle to U-threat characterizes fear disorder patients and is malleable to treatment with CBT but not SSRIs within fear patients. Startle to U-threat may therefore reflect an objective, psychophysiological indicator of fear disorder status and CBT treatment response.